Expanding Scope of Practice for Ontario Optometrists - Emily Catherine Bray; Ivy Bourgeault (McMaster University Library Press, 2017)
In 2011, The Optometry Act, 1991 was amended to include The Designated Drugs and Standards of Practice Regulation which expanded the scope of practice for Ontario optometrists to include prescribing privileges from a specific list of drugs. The goals of the optometry reform were to increase access to care, decrease burden on medical and hospital resources and allow optometrists to practice to their full scope. The policy response was spurred by a recommendation from the Health Professions Regulatory Advisory Council and the prescribing precedence in other Canadian jurisdictions. Bill 171, The Health Systems Improvement Act, amended The Optometry Act, 1991, Section 4 to include the authorized act of prescribing designated drugs, while The Designated Drugs and Standards of Practice, passed on 6 April 2011, listed the individual drugs optometrists are authorized to prescribe. The resulting response of a specific list of authorized drugs was seen as a limiting and inflexible system that will require changes as newer drugs are developed.  La Loi de 1991 sur les optométristes a été modifiée en 2011, afin d'intégrer le règlement sur les médicaments enregistrés et les normes de pratiques (Designated Drugs and Standards of Practice Regulation) élargissant le champ d'activité des optométristes en Ontario aux privilèges de prescription d'une liste explicite de médicaments. La réforme de l'optométrie avait pour objectifs d'augmenter l'accès aux soins, de diminuer la charge de travail pesant sur les ressources médicales et hospitalières et de permettre aux optométristes de pratiquer pleinement leur profession. L'initiative politique a été provoquée par la recommandation du Conseil consultatif de réglementation des professions de la santé ainsi que par l'existence de tels privilèges dans d'autres provinces canadiennes. Alors que le projet de loi 171, ou Loi de 2007 sur l'amélioration du système de santé, avait modifié l'article 4 de la Loi de 1991 sur les optométristes en ouvrant la possibilité de prescrire des médicaments enregistrés, le règlement sur les médicaments enregistrés et les normes de pratiques (Designated Drugs and Standards of Practice Regulation), adopté le 6 Avril 2011, énumère les médicaments individuels que les optométristes sont autorisés à prescrire. La réponse politique consistant à définir une liste explicite de médicaments autorisés a été jugée limitative et rigide, qui réclamera des aménagements successifs pour toute innovation médicamenteuse.